2021
DOI: 10.3389/fphar.2021.713007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lipid-Lowering Drugs of Different Intensity on Clinical Outcomes: A Systematic Review and Network Meta-Analysis

Abstract: There have been many meta-analyses for statins, ezetimibe and proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) to evaluate clinical outcomes, but the efficacy and safety of different intensity of these three drugs on clinical outcomes was absent. PCSK9i, ezetimibe, and statins were divided into seven interventions as follows: including PCSK9i + high-intensity statins (P9i+HT), PCSK9i + moderate-intensity statins (P9i+MT), ezetimibe + high-intensity statins (Eze+HT), ezetimibe + moderate-intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Our results are consistent with prior evidence on lipid-lowering therapies. For instance, a network meta-analysis by Ma et al showed larger relative risk reduction in cardiovascular outcomes by addition of PCSK9 inhibitor on statin than ezetimibe 37. Ezetimibe has been shown to reduce risk of non-fatal myocardial infarction and stroke, but not mortality (moderate to high certainty) 3435.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with prior evidence on lipid-lowering therapies. For instance, a network meta-analysis by Ma et al showed larger relative risk reduction in cardiovascular outcomes by addition of PCSK9 inhibitor on statin than ezetimibe 37. Ezetimibe has been shown to reduce risk of non-fatal myocardial infarction and stroke, but not mortality (moderate to high certainty) 3435.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies primarily concentrated on the comparative analysis of different lipid‐lowering drugs 5,35,36 . Nevertheless, our DCE study is unique in that it evaluates the significance of these differences from the patient and physician perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies primarily concentrated on the comparative analysis of different lipid‐lowering drugs. 5 , 35 , 36 Nevertheless, our DCE study is unique in that it evaluates the significance of these differences from the patient and physician perspectives. Despite the favourable efficacy, safety and administration frequency of PCSK9 inhibitors, our study found that subcutaneous injections were a source of distress for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Everything started with two pivotal studies – the Lipid Research Clinics Coronary Primary Prevention Trial (LRC-CPPT) published in 1984 [ 1 ] that showed the proof-of-concept of lipid lowering and confirmed that reducing LDL-C levels can diminish the incidence of coronary heart disease (CHD) morbidity and mortality in men at high risk for CHD, and the 4S study [ 23 ] that 10 years later confirmed the role of statins in reduction of all-cause mortality. Subsequently, hundreds of studies confirmed these results, and now statins are essential drugs in both primary ( Figure 2 A ) and secondary ( Figure 2 B ) prevention of ASCVD, effectively prolonging patients’ lives [ 24 , 25 ].…”
Section: Therapy: Statins – the Gold Standard In Lipidologymentioning
confidence: 96%
“… The impact of statin use on the prognosis of patients in primary ( A ) and secondary ( B ) prevention [ 24 , 25 ] …”
Section: Therapy: Statins – the Gold Standard In Lipidologymentioning
confidence: 99%